PERANCANGAN SISTEM INFORMASI MONITORING PRESENSI SISWA (STUDI KASUS: SMK XYZ) - Angelina Tiur Pakpahan; Riad Sahara (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Regarding to the research that had been done by Michael Weitzman and colleagues, children who are frequently or persistently absent from school tend to perform poorly in school and are likely to drop out before graduation from school. The parents action for this kind of problems are highly needed, but nowadays, the implemented system by school as the education provider does not good enough to connect the educational institution with parents faster and efficiently, so that the related problems that occur could not handled earlier. Thus, it is important to create an information system based on technology that could be able to connect parents and education institution faster and efficient. The used methods to support this research are designing system, iterate the related researches, and retrieve data from one of National-Vocational High School in Jakarta. As the system flow, the education provider input the presence attendances of their student on the system interface, system automatically record it and then directly send it to the parents by real time. By building this system, the education provider expected to be able to handle this kind of cheats related with student absence faster, easier, and efficient, so that the unexpected problems could be able to minimize either vanished at all.